Zinc oxide nano-particles as sealer in endodontics and its sealing ability - Maryam Javidi; Mina Zarei; Neda Naghavi; Majed Mortazavi; Amir Hosein Nejat (Wolters Kluwer Medknow Publications, 2014)
Aims: The aim of this study was to evaluate the sealing ability of new experimental nano-ZOE-based sealer. Settings and Design: Three types of nano-ZOE-based sealer (calcined at different temperatures of 500, 600 and 700°C) with two other commercially available sealers (AH26 and micro-sized zinc oxide eugenol sealer) were used. Materials and Methods: Zinc oxide nano-particles were synthesized by a modified sol-gel method. The structure and morphology of the prepared powders were characterized using x-ray diffraction (XRD) and transmission electron microscopy (TEM) techniques. The instrumented canals of 60 single-rooted teeth were divided into five groups (n = 10), with the remaining ten used as controls. The canals were filled with gutta-percha using one of the materials mentioned above as sealer. After 3, 45 and 90 days, the samples were connected to a fluid filtration system. Statistical Analysis Used: The data were analyzed using Student's t-test. Results: The XRD patterns and TEM images revealed that all the synthesized powders had hexagonal wurtzite structures with an average particle size of about 30-60 nm at different calcination temperatures. Microleakage in AH26 groups was significantly more than that in three groups of ZnO nano-particles at all the three evaluation intervals. Apical microleakage of ZnO micro-powders was significantly more than that of all the materials, but the sealing ability of ZnO nano-powder sealers did not differ significantly. Conclusion: The results of this study showed that the synthesized ZnO nano-powder sealers are suitable for use as a nano-sealer in root canal therapy to prevent leakage; however, further studies should be carried out to verify their safety.